2013
DOI: 10.1155/2013/487232
|View full text |Cite
|
Sign up to set email alerts
|

Khat Chewing among Students of Higher Education in Jazan Region, Saudi Arabia: Prevalence, Pattern, and Related Factors

Abstract: Objectives. (1) To estimate the prevalence and behavioral patterns of Khat chewing and (2) to investigate factors that influenced the pattern of Khat use among undergraduate students in different higher education institutions in Jazan region, Saudi Arabia. Materials and Methods. A cross-sectional study using a pretested structured self-administered quantitative questionnaire was used to collect data. SPSS version 17 software program was used for data analysis. Results. The overall current Khat chewing prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
44
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 15 publications
14
44
5
Order By: Relevance
“…The result is different from the findings reported by Alsanosy and his peers in Jazan region [5] that most (43.8%) of the participants chewed khat in their houses. This might be due to that the participants in the previous study area were using dormitory services in their home that gave them a good opportunity for chewing at their home freely.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The result is different from the findings reported by Alsanosy and his peers in Jazan region [5] that most (43.8%) of the participants chewed khat in their houses. This might be due to that the participants in the previous study area were using dormitory services in their home that gave them a good opportunity for chewing at their home freely.…”
Section: Discussioncontrasting
confidence: 99%
“…This might be due to that the participants in the previous study area were using dormitory services in their home that gave them a good opportunity for chewing at their home freely. Similarly, in our study setting most (85%) students reported that they can find khat easily, which is almost consistent with the study done in Jazan higher education [5]. This shows that khat is available for students who want to chew.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations